1994
DOI: 10.1111/j.1476-5381.1994.tb13132.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of DAU 6215, a novel 5‐hydroxytryptamine3 (5‐HT3) antagonist on electrophysiological properties of the rat hippocampus

Abstract: 1 The aim of the present study was to test the effects of DAU 6215 (endo-N-(8-methyl-8-azabicyclo-[3.2.1]-octo-3-yl)-2,3-dihydro-2-oxo-lH-benzimidazole-1-carboxamide hydrochloride), a newly synthesized, selective aminophosphonovaleric acid (APV; 501M) and 6,7-dinitroquinoxaline-2,3-dione (DNQX; 25 tiM), and were elicited by the selective 5-HT3 agonist, 2-methyl-5-HT (2-Me-5-HT, 50 pM).5 The increase in frequency of s.p.s.ps induced by 5-HT was significantly antagonized by DAU 6215 in 70% of the cases, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
2

Year Published

1995
1995
2008
2008

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 44 publications
3
30
0
2
Order By: Relevance
“…In contrast, activation of 5-HT 3 receptors enhances GABA release in the hippocampus (Yakel and Jackson, 1988;Ropert and Guy, 1991;Corradetti et al, 1992;Kawa, 1994;Maeda et al, 1994;Passani et al, 1994). In this study, we tested the hypothesis that these two receptors, having opposite effects on GABA neurotransmission, might be present in the same hippocampal neurons.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In contrast, activation of 5-HT 3 receptors enhances GABA release in the hippocampus (Yakel and Jackson, 1988;Ropert and Guy, 1991;Corradetti et al, 1992;Kawa, 1994;Maeda et al, 1994;Passani et al, 1994). In this study, we tested the hypothesis that these two receptors, having opposite effects on GABA neurotransmission, might be present in the same hippocampal neurons.…”
Section: Introductionmentioning
confidence: 80%
“…Earlier electrophysiological studies have demonstrated that activation of the 5-HT 3 receptor results in enhanced GABAergic neurotransmission in cultured hippocampal neurons (Yakel and Jackson, 1988) and hippocampal slices (Ropert and Guy, 1991;Corradetti et al, 1992;Kawa, 1994;Maeda et al, 1994;Passani et al, 1994). Serotonin directly excites GABAergic interneurons via the 5-HT 3 receptor and consequently increases the frequency of inhibitory synaptic events recorded in CA1 pyramidal cells of rat hippocampal slices (Ropert and Guy, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Agonist effects were blocked by the GABAA antagonist bicuculline, and antagonist-induced augmentation of LTP was blocked by atropine. Passani et al (1994) report that the 5-HT3 antagonist DAU 6215 reversed 5-HT-induced inhibition of LTP in the Schaffer collateral-CA1 junction. Direct links between theta, LTP, 5-HT3 receptor activation and learning have recently been demonstrated by Staubli and Xu (1995).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to these mixed effects on 5-HT release, electrophysiological studies suggest that 5-HT3 receptors play an important role in evoked and spontaneous hippocampal neuronal firing, in conjunction with muscarinic and GABA receptors. 5-HT3 antagonists have been shown to facilitate long-term potentiation (LTP) in the mossy fibre CA3 system and in the Schaffer collateral-CA1 system, and to increase spontaneous theta in the CA1 field (Maeda et al 1994;Passani et al 1994;Staubli and Xu 1995).…”
mentioning
confidence: 99%
“…Activation of α7 nACh receptors mediates strong excitatory effects that result in an increase of GABAergic neurotransmission in the hippocampus (Jones and Yakel, 1997;Alkondon et al, 1998;Frazier et al, 1998a,b;McQuiston and Madison, 1999;Shao and Yakel, 2000;Sudweeks and Yakel, 2000). Similarly, activation of the 5HT 3 receptor results in enhanced GABAergic neurotransmission in cultured hippocampal neurons (Yakel and Jackson, 1988) and in hippocampal slices (Ropert and Guy, 1991;Corradetti et al, 1992;Kawa, 1994;Maeda et al, 1994;Passani et al, 1994). Moreover, 5-HT was shown to directly excite GABAergic interneurons via the 5HT 3 receptor and consequently to increase the frequency of inhibitory synaptic events recorded in CA1 pyramidal cells of rat hippocampal slices (Ropert and Guy, 1991).…”
Section: Hippocampal α7 Nach/cb1/5ht3 a /Cck Interneuronsmentioning
confidence: 99%